Association of 32 type 1 diabetes risk loci in Pakistani patients. Issue 1 (April 2015) - Kiani, Aysha Karim; John, Peter; Bhatti, Attya; Zia, Asima; Shahid, Gulbin; Akhtar, Parveen; Wang, Xingbin; Demirci, F. Yesim; Kamboh, M. Ilyas
Highlights First genetic study of T1D in Pakistani subjects. Evidence of T1D risk loci. Shared T1D loci between Caucasians and Pakistani.